2019
DOI: 10.1177/000313481908501012
|View full text |Cite
|
Sign up to set email alerts
|

Esophageal Trauma: Analysis of Incidence, Morbidity, and Mortality

Abstract: Traumatic esophageal injury is a highly lethal but rare injury with minimal data in the trauma population. We sought to provide a descriptive analysis of esophageal trauma (ET) to identify the incidence, associated injuries, interventions, and outcomes. We hypothesized that blunt trauma is associated with higher risk of death than penetrating trauma. The Trauma Quality Improvement Program (2010–2016) was queried for patients with ET. Patients with blunt and penetrating trauma were compared using chi-square and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…Esophageal injuries are only estimated to account for 0.02–1% of all traumatic injuries, with many individuals dying on scene from exsanguination secondary to co-injury of the great vessels ( 16 , 17 - 23 ). If present these injuries pose significant morbidity (upwards of 70%) and mortality (40–53%) ( 17 , 21 , 24 ). Esophageal trauma can be categorized based on location (cervical, thoracic or abdominal), as well as mechanism (blunt or penetrating) ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Esophageal injuries are only estimated to account for 0.02–1% of all traumatic injuries, with many individuals dying on scene from exsanguination secondary to co-injury of the great vessels ( 16 , 17 - 23 ). If present these injuries pose significant morbidity (upwards of 70%) and mortality (40–53%) ( 17 , 21 , 24 ). Esophageal trauma can be categorized based on location (cervical, thoracic or abdominal), as well as mechanism (blunt or penetrating) ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…If present these injuries pose significant morbidity (upwards of 70%) and mortality (40–53%) ( 17 , 21 , 24 ). Esophageal trauma can be categorized based on location (cervical, thoracic or abdominal), as well as mechanism (blunt or penetrating) ( 24 ). Esophageal injury in trauma is thought to be upwards of 16 times more common in penetrating injuries where the cervical esophagus is most commonly affected ( 23 - 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…Traumatic esophageal injury reportedly occurs in only 0.01% of chest injuries 1 . However, once esophageal perforation occurs, it can be life-threatening and should be cautiously diagnosed.…”
Section: Fracture: a Case Report And Literature Reviewmentioning
confidence: 99%
“…Penetrating and blunt injuries to the esophagus remain rare, with the majority of injuries being iatrogenic or endoluminal in origin. [2][3][4][5][6][7] Penetrating trauma causes more esophageal injuries than blunt trauma, though these still occur in only .7% of patients with penetrating chest wounds. 9 Several reviews from both the National Trauma Data Bank and the Trauma Quality Improvement Program have noted a high percentage of additional organs injured, such as ribs and lungs, depending on the mechanism and due to the location of the esophagus deep in the thorax.…”
Section: Epidemiologymentioning
confidence: 99%
“…7 Morbidity and mortality rates remain high due to associated vascular injuries in the neck and chest and are similar after blunt or penetrating trauma. 2 Aiolfi et al 6 found that age >50, thoracic injury, high-grade esophageal injury (OIS IV–V), hypotension on admission, and GCS <9 were independent risk factors for increased mortality.…”
Section: Epidemiologymentioning
confidence: 99%